Hyaluronic acid: Additional biochemical marker in the diagnosis of biliary atresia - Nuthapong Ukarapol (2018)
Background: The purpose of the present paper was to evaluate the value of biochemical markers, including conventional liver function tests, γ-glutamyl transferase (GGT), and hyaluronic acid (HA), in the diagnosis of neonatal cholestasis. Methods: Infants with neonatal jaundice were consecutively enrolled during 1 year period. The patients were diagnosed as having biliary atresia (BA) if there was either bile ductular proliferation in the portal tracts, atretic common bile duct/gallbladder, or evidence of bile duct obstruction demonstrated by liver pathology or intraoperative cholangiography, respectively. Serum HA was measured using an enzyme-linked immunosorbent assay-based test. Results: A total of 25 patients diagnosed as having BA (n = 10), neonatal hepatitis (NH; n = 9), choledochal cyst (n = 3) and parenteral nutrition-induced cholestasis (n = 3), were studied. The age at diagnosis was not significantly different between groups. Only GGT and HA were significantly elevated in the patients with BA when compared to NH (P = 0.02, P = 0.03, respectively). In BA, the median value of serum HA was 514 ng/mL (range 19-4476 ng/mL), compared to 50 ng/mL (range 19-315 ng/mL) in NH. Additionally, the serum HA level was much higher in children with choledochal cyst. Conclusion: HA could be considered as a complementary biochemical marker for evaluating infants with prolonged jaundice. © 2007 Japan Pediatric Society.